Elucidation of parallel microstructure and evolution of magnetic properties in nickel zinc ferrite - Mustaffa, Muhammad Syazwan (2013)
The relationship between microstructural properties and magnetic characteristics of nickel zinc ferrite (Ni0.6Zn0.4Fe2O4) is the focus of interest in this research work. This interest has arisen from the fundamental scientific enquiry on the evolution of microstructure with the magnetic properties in between 1 nm-to-1 μm grain size region neglected by ferrites researchers for more than 80 years. Hence, here in this research work, we intend to track down the evolution of magnetic properties parallel to the microstructural changes in Ni0.6Zn0.4Fe2O4. Nickel zinc ferrite (Ni0.6Zn0.4Fe2O4) was prepared via High-energy ball milling (HEBM) using a SPEX8000D mill. Using single-sample sintering (SSS), the sample was repeatedly sintered with increasing temperature within the range 600oC until 1200oC with an increment of 25oC in ambient air condition for 10 hours. After each sintering, the resulting changes in the materials were observed. The completion of solid state reaction was confirmed by using X-ray diffraction (XRD). Scanning Transmission Electron Microscopy (STEM) was employed to confirm the particle size of the powder achieved. The evolution of microstructural properties of the sintered toroid was determined by using a Field Emission Scanning Electron Microscopy (FESEM) machine. The magnetic studies were carried out by using an Impedance Analyzer for AC response parameters, B–H Hysteresisgraph for B–H hysteresis loops and Precision Impedance Analyzer for Curie temperature measurements. The Archimedes principle was applied to determine the density of the toroid. The X-ray diffraction (XRD) patterns showed a single phase have been formed as early as 600°C and above and the intensity peaks increased with sintering temperature,indicating an increase in the degree of crystallinity. The morphological studies show a microstructural evolution (larger grain size) with the increased in sintering temperature. Grain size and density increased with increasing sintering temperature while the porosity decreased with increasing sintering temperature. An integrated analysis of phase, microstructural and hysteresis data points to the existence of three distinct shape-differentiated groups of B–H hysteresis loops which belong to the sample with weak, moderate and strong magnetism. The coercivity-vs-grain size plot reveals the critical single-domain-to-multidomain grain size to be about ~ 400 nm. The real permeability, μ’ and loss factor, μ”, increase with grain size due to increase in sintering temperature. A scrutiny of the permeability components, μ’ and μ”, also reveals three different groups which can be explained similarly by phase purity, microstructural data and crystallinity as in the B–H hysteresis case. The microstructural grain growth, as revealed for the first time by this research work is shown to be a process of multiple activation energy barriers. The Curie temperature gave the same value for each sintering temperature which means it remained relatively stable and unaffected by the above evolutions. It is due to an intrinsic property which depends only on compositional stoichiometry and crystal structure.